Empirical analysis of mobile broadband adoption in major six countries from the view of competition policy - Sobee Shinohara; Hiroyuki Morikawa; Masatsugu Tsuji (International Telecommunications Society (ITS), 2014)
The purpose of this paper is to study competition policy on mobile broadband, consisting of 3G and 4G (LTE).Currently mobile broadband has been developing rapidly and its access speed amounts to 150Mbps for the latest 4G, which is similar to fixed broadband. This paper analyzesthe factors affect the mobile broadband adoption in major six countries,such as the U.S., UK, France, Germany, Japan, and Korea,those cover more than fifty percentof total population and adoption ratio of OECD 34 member countries. The factors examined here includeHHI and frequency auction as completionpolicy, FTTH adoption, FMC (Fixed mobile convergence), and launching Android and iPhone, inaddition to economic variables such as price and income. Panel data analysis showed that smartphone, competition among telecommunicationcarriers observed by HHI and FTTH affect mobile broadband adoption. This result provides important basis for competition policy on mobile broadband in each country.
Keywords: 330; Mobile Broadband; Competition Policy; Smartphone; iPhone; Android; Feature Phone; 3G; 4G; FTTH; Panel Data Analysis